2022
DOI: 10.23887/jet.v6i4.45471
|View full text |Cite
|
Sign up to set email alerts
|

Role-Playing Game (RPG) to Increase Student's Learning Motivation

Abstract: Online learning during the Covid-19 pandemic made teachers and students study separately and resulting in low student learning enthusiasm. This study aims to create a learning media Role-Playing Game (RPG) to increase student motivation. This research is Research and Development with the Alessi & Trollip model. The population in this study amounted to 512. The sampling technique was a simple random sampling of 120 students. At the alpha test stage, the media was validated by 3 media experts and 3 material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Also, this is in line with Zimmerman (2000), one such approach involves engaging in continuous monitoring and reviewing all the activities they have undertaken, thereby re-evaluating the completed tasks. Also aligned with research that conducted by Sholichah et al (2022), the developed educational game utilizing RPG elements has been demonstrated to effectively enhance students' motivation for learning, leading to notable improvements in their overall engagement and enthusiasm for the educational content.…”
Section: B Discussionmentioning
confidence: 73%
“…Also, this is in line with Zimmerman (2000), one such approach involves engaging in continuous monitoring and reviewing all the activities they have undertaken, thereby re-evaluating the completed tasks. Also aligned with research that conducted by Sholichah et al (2022), the developed educational game utilizing RPG elements has been demonstrated to effectively enhance students' motivation for learning, leading to notable improvements in their overall engagement and enthusiasm for the educational content.…”
Section: B Discussionmentioning
confidence: 73%